Antenatal magnesium sulfate and the need for mechanical ventilation in the first three days of life - Ololade Okito; Adeolu Aromolaran; Beri Massa-Buck; Dinan Abdelatif; Hany Aly; Mohamed A. Mohamed (Elsevier, 2023)
Background: Antenatal administration of magnesium sulfate (MgSO4) to women in preterm labor has gained widespread use. This study examined the relationship between MgSO4 exposure with neonatal respiratory outcomes. Methods: Very low birth weight (VLBW) infants exposed to antenatal MgSO4 were included. Infants who were intubated anytime during the first three days of life were compared to those who were not intubated regarding their demographic and clinical characteristics, MgSO4 therapy, immediate respiratory outcomes, and occurrence of intraventricular hemorrhage (IVH) using student t-test, chi square testing and logistic regression analysis to control for confounding variables. Correlation coefficient of MgSO4 cumulative dose given and duration of infusion with delivery room resuscitation and need for mechanical ventilation in the first 3 days of life were also calculated. Multilinear regression analysis was used to control for confounding factors. Results: Intubated group included 96 infants while non-intubated group included 171 infants. Although, intubated group has younger gestational age (26 vs. 29 weeks, p < 0.01) and lower birth weight (786 vs. 1115 g (g), p < 0.01), there were no significant differences between groups in regard to MgSO4 cumulative dose (24 vs. 27 g, p = 0.29), infusion time (14.6 vs. 18 h, p = 0.19) or infants' serum magnesium level (2.6 vs. 2.8 milliequivalents (mEq)/L p = 0.86). There was no correlation between cumulative MgSO4 dose with endotracheal intubation or cardiac resuscitation in the delivery room (cc: −0.03, p = 0.66; and 0.02, p = 0.79, respectively) or the need for mechanical ventilation in the first 3 days of life (cc: −0.04 to −0.07, p = 0.21-0.51). In addition, there was no relationship between MgSO4 dose, duration of infusion, or infant's serum magnesium level and occurrence of IVH. Conclusion: Regardless of dose or duration of infusion, antenatal MgSO4 exposure is not associated with increased intubation or mechanical ventilation early in life.